The added value of real options analysis for climate change adaptation. (4th March 2020) - Wreford, Anita; Dittrich, Ruth; van der Pol, Thomas D.
Abstract: Climate change adaptation investment decisions can be made more efficiently if uncertainty and new information are considered in their economic appraisal. Real options analysis (ROA) is a robust decision‐making tool that allows for the incorporation of both uncertainty and new information. In this opinion article, we argue that ROA is a valuable tool, providing the analysis is designed to reflect the real‐world characteristics of the decision context. We highlight the differences between traditional risk‐based ROA, and scenario‐based ROA, and discuss the relative merits of the approaches from the perspective of their assumptions and use of climate information. We also emphasize the need for increased co‐development of ROA design and applications with end‐users. Given the large climate uncertainties for long‐term adaptation planning, we suggest that an emerging strand of scenario‐based ROA methods offers ways to help identify and conditionally value flexibility without aggregating values into precise expected values across states of the world. This article is categorized under: Climate Economics > Iterative Risk‐Management Policy Portfolios Abstract : Real options analysis (ROA) can enable economically efficient adaptation investment decision‐making. Through identifying and valuing flexibility, ROA can support decisions in an uncertain future.